Descriptive analysis of colour Doppler echocardiography results in neonates with congenital heart disease in eastern China: a retrospective cohort study - Wang, Hui; Guo, Qifeng; Yu, Xiuhua (Frontiers in Pediatrics, 2025)
IntroductionColour Doppler echocardiography (Echo) is the preferred examination method for cardiac health in newborns. Since 2019, an neonatal echocardiographic screening program has been conducted for all newborns in Hangzhou, China. Herein, we conducted a descriptive analysis of all newborns screened at our hospital, aiming to explore the prevalence in neonatal Echo abnormality.MethodsThe data of 813 neonates who underwent Echo between 2019 and 2024 were retrospectively analysed. Subsequently, we compared the differences in clinical data between neonates with positive (positive neonates) and negative (negative neonates) screening results and further analysed the correlation between Echo results and gestational age at delivery, maternal age, sex, and weight.ResultsThe overall prevalence of neonatal Echo abnormality was 83.8%. No significant differences in the clinical data were noted between positive and negative neonates. Multivariate logistic regression analysis subsequently revealed that only gestational age at delivery was an independent influencing factor for Echo abnormality [odds ratio (OR) = 0.813, P < 0.05]. Neonatal birth weight was found to be an independent influencing factor for patent ductus arteriosus (OR = 1.001, P < 0.05), whereas neonatal sex, gestational age at delivery, and maternal age were not identified as independent influencing factors for certain abnormalities.DiscussionThis study highlights the importance of early pregnancy detection through timely pregnancy testing, facilitating early prenatal care for women and thereby reducing the risk of premature birth and low birth weight. Neonatal Echo screening holds substantial value in early detection, enabling the monitoring of cardiac abnormalities and facilitating the provision of early intervention measures.